Proteomics of the Dark-Ventral-Patch Sexual Signal in Male Red Deer - Camilla Broggini; Paula V. Huertas-Abril; Alberto Membrillo; Eva de la Peña; Nieves Abril; Juan Carranza (Animals)
Sexual signals in animals encompass a variety of forms including visual, acoustic, and chemical signals that are fundamental for intra- and interspecific communication, including sexual selection processes. Among these, odor signals play a critical role. Chemical compounds involved in sexual signaling vary in nature, with lipids and proteins being particularly important. In the male Iberian red deer (Cervus elaphus hispanicus), the dark ventral patch has been identified as a key sexual signal during mating competition, associated with specific chemical compounds deposited during urination. Hair plays a significant role in this signaling due to its ability to retain compounds on the scales of the hair cuticle. In this study, we used a shotgun proteomic approach to investigate whether the ventral patch hair retains proteins on its surface that could reveal metabolic and cell-signaling adaptations potentially related to reproductive activity. Characterization of the origin and functionality of the proteins found in the hair of the dark ventral patch of male red deer, and their relationship to distinct metabolic pathways, provides an initial understanding of the potential role of these compounds in chemical communication in red deer intrasexual competition for mates.